Too Old for Computers? The Longitudinal Relationship Between Stereotype Threat and Computer Use by Older Adults - Mariano, João; Marques, Sibila; Ramos, Miguel R.; Gerardo, Filomena; de Vries, Hein (Frontiers in Psychology, 2020)
Besides having lower rates of technology adoption than younger age groups, older adults are commonly stereotyped as lacking technological ability. Stereotype threat, the fear of confirming negative stereotypes targeting their social group, may lead individuals to distance themselves from the stereotyped domain. This suggests that older adults may underuse computer technology due to stereotype threat. A sample of 86 community-dwelling older adults (Mage = 78.47, SDage = 7.92) participated in a two-wave longitudinal study aiming to examine the relationship between stereotype threat and computer use in this age group. An autoregressive cross-lagged panel analysis was conducted using structural equation modeling. As expected, stereotype threat predicted lower levels of computer use a year and a half later. In turn, computer use was unrelated to the later experience of stereotype threat in this domain. These findings suggest that stereotype threat may undermine computer adoption in late adulthood, thus contributing to perpetuate the digital inequalities between younger and older generations.